Diagnostic investigation of new disease syndromes in farmed Australian saltwater crocodiles (Crocodylus porosus) reveals associations with herpesviral infection. (May 2016) - Shilton, Catherine M.; Jerrett, Ian V.; Davis, Steven; Walsh, Susan; Benedict, Suresh; Isberg, Sally R.; Webb, Grahame J. W.; Manolis, Charlie; Hyndman, Timothy H.; Phalen, David; Brown, Gregory P.; Melville, Lorna
Since 2006, 3 new disease syndromes have emerged in farmed saltwater crocodiles ( Crocodylus porosus ) in the Northern Territory of Australia. We describe the syndromes through a retrospective study of laboratory findings from 187 diagnostic cases submitted to Berrimah Veterinary Laboratories between 2005 and 2014. The first syndrome was characterized by conjunctivitis and/or pharyngitis (CP), primarily in hatchlings. Herpesviruses were isolated in primary crocodile cell culture, or were detected by PCR directly from conjunctiva or pharyngeal tissue, in 21 of 39 cases of CP (54%), compared with 9 of 64 crocodiles without the syndrome (14%, p < 0.0001). Chlamydiaceae were detected by PCR in conjunctiva or pharyngeal tissue of 55% of 29 CP cases tested, and of these, 81% also contained herpesvirus. The second syndrome occurred in juveniles and growers exhibiting poor growth, and was characterized histologically by systemic lymphoid proliferation and nonsuppurative encephalitis (SLPE). Herpesviruses were isolated or detected by PCR from at least 1 internal organ in 31 of 33 SLPE cases (94%) compared with 5 of 95 crocodiles without the syndrome (5%, p < 0.0001). The third syndrome, characterized by multifocal lymphohistiocytic infiltration of the dermis (LNS), occurred in 6 harvest-sized crocodiles. Herpesviruses were isolated from at least 1 skin lesion in 4 of these 6 cases. Although our study revealed strong associations between herpesvirus and the CP and SLPE syndromes, the precise nature of the role of herpesvirus, along with the pathogenesis and epidemiology of the syndromes, requires further investigation.